Early childhood obesity: Association with healthcare expenditure in Australia. Issue 8 (6th July 2016) - Hayes, Alison; Chevalier, Anna; D'Souza, Mario; Baur, Louise; Wen, Li Ming; Simpson, Judy
Abstract : Objective: To determine whether overweight or obesity among children (aged 2 to ≤5 years) is associated with direct healthcare costs, after adjusting for child, household, and socioeconomic characteristics. Methods: A longitudinal cohort analysis was performed in 350 children aged 2 years assessed over 3 years of follow‐up. Child weight status was determined from mean BMI z ‐scores at 2, 3.5, and 5 years, and healthcare utilization including medicines, nonhospital, hospital, and emergency care was determined by data linkage. Using adjusted multivariable regression analyses, the relationship between total 3‐year healthcare costs and weight status was examined. Observations took place in Sydney, Australia, between 2011 and 2014. Results: After adjustment for significant maternal and sociodemographic characteristics, healthcare costs of children with obesity (BMI z ‐score >2SD) were 1.62 (95% CI 1.12‐2.34, P = 0.01) times those of children with healthy weight. However, costs of overweight children were similar to those of healthy weight ( P = 0.96). The additional 3‐year costs of healthcare for a child with obesity compared with healthy weight were $AUD 825 (95% CI $135‐$2, 117) for general patients and $AUD 1332 (95% CI $174‐$4, 280) for concession card holders. Conclusions: Prevention of obesity in early childhood may have concurrent benefits in reducing healthcare expenditure.